Analisis Upaya Guru Kelas dalam Menangani Kesulitan Membaca pada Siswa Kelas V SDN Bojongsari 04 - Yuliani Dwi Tiara; Setiyoko Tri Didik; Triputra Romli Dedi (EduInovasi: Journal of Basic Educational Studies, 2026)
Reading literacy is a fundamental foundation for elementary school students to understand various subjects, but in reality, upper-grade students still face functional reading difficulties. This study aims to analyze the forms of reading difficulties, contributing factors, and the efforts and constraints of classroom teachers in addressing these issues among fifth-grade students at SDN Bojongsari 04. The method used in this research is descriptive qualitative, with data collection through interviews with the fifth-grade teacher. The results indicate that the primary difficulty is the students' inability to string words together and comprehend reading content, despite being familiar with letters. Contributing factors include low internal reading interest, a lack of parental guidance, and excessive gadget use at home. Teachers have made efforts through guided reading methods, extra hours, and providing appreciation, but effectiveness is hindered by time constraints and a lack of cooperation with parents. The study concludes that stronger synergy between schools and families is essential to overcome students' literacy barriers sustainably.